Crime e violência no Tocantins (1889-1930) - Santos , Samuel Antonio Carvalho dos (2023)
The present research aims to reveal the crimes that occurred in the period of the First Republic (1889-1930). In the period, the social context of Tocantins was marked by the concentration of powers in the hands of landowner colonels. In the village of São José do Duro (Dianópolis - TO) the Wolney family carried out a crime of national repercussion. From regional and national newspapers, such as “ O Correio Oficial de Goiás”, “A Tribuna Livre”, “Jornal de Notícias”, “Norte de Goiás” and “Diário do Maranhão”, we identified stories of crimes, thefts, robberies, aggressions, desertion and murders, evidencing the presence of violence and criminal practices that occurred in Goiás, mainly in its northern region, and the current state of Tocantins. These periodicals help us, above all, to know facts, characters involved, motivations and court rulings. Another essential source for the work is the work O Tronco by Bernardo Élis. From it, it was possible to reconstruct the crime that occurred in Vila do Duro and understand the context of the region. Thus, the work seeks to contribute to the debate about crimes and acts of violence.